ВНЕДРЕНИЕ ИНФОРМАЦИОННЫХ ТЕХНОЛОГИЙ В БИБЛИОТЕКАХ С УЧЕТОМ ОЦЕНКИ ИХ ЭФФЕКТИВНОСТИ (Библиосфера)
The stages of information technologies (IT) implementation (the development of IT-strategy of library, a detailed IT-planning for objects, investigation of influenced object, IT choice taking into account the efficiency, staff training, implementation of IT, analysis of implementation results) are considered. A model of IT implementation with the account of their efficiency is proposed.